Brain-derived tau oligomer polymorphs: distinct aggregations, stability profiles, and biological activities - Filippa Lo Cascio; Suhyeorn Park; Urmi Sengupta; Nicha Puangmalai; Nemil Bhatt; Nikita Shchankin; Cynthia Jerez; Naomi Moreno; Alice Bittar; Rhea Xavier; Yingxin Zhao; Cankun Wang; et al. (Communications Biology)
Abstract Aggregation of microtubule-associated tau protein is a distinct hallmark of several neurodegenerative disorders such as Alzheimer’s disease (AD), dementia with Lewy bodies (DLB), and progressive supranuclear palsy (PSP). Tau oligomers are suggested to be the primary neurotoxic species that initiate aggregation and propagate prion-like structures. Furthermore, different diseases are shown to have distinct structural characteristics of aggregated tau, denoted as polymorphs. Here, we investigate the structural and functional differences of amplified brain-derived tau oligomers (aBDTOs) from AD, DLB, and PSP. Our results indicate that the aBDTOs possess different structural and morphological features that impact neuronal function, gene regulation, and ultimately disease progression. The distinct tau oligomeric polymorphs may thus contribute to the development of clinical phenotypes and shape the progression of diseases. Our results can provide insight into developing personalized therapy to target a specific neurotoxic tau polymorph.